Falls risk assessment outcomes and factors associated with falls for older Indigenous Australians. (13th September 2016) - Hill, Keith D.; Flicker, Leon; LoGiudice, Dina; Smith, Kate; Atkinson, David; Hyde, Zoë; Fenner, Stephen; Skeaf, Linda; Malay, Roslyn; Boyle, Eileen
Abstract: Objective: To describe the prevalence of falls and associated risk factors in older Indigenous Australians, and compare the accuracy of validated falls risk screening and assessment tools in this population in classifying fall status. Method: Cross‐sectional study of 289 Indigenous Australians aged ≥45 years from the Kimberley region of Western Australia who had a detailed assessment including self‐reported falls in the past year (n=289), the adapted Elderly Falls Screening Tool (EFST; n=255), and the Falls Risk for Older People‐Community (FROP‐Com) screening tool (3 items, n=74) and FROP‐Com falls assessment tool (n=74). Results: 32% of participants had ≥1 fall in the preceding year, and 37.3% were classified high falls risk using the EFST (cut‐off ≥2). In contrast, for the 74 participants assessed with the FROP‐Com, only 14.9% were rated high risk, 35.8% moderate risk, and 49.3% low risk. The FROP‐Com screen and assessment tools had the highest classification accuracy for identifying fallers in the preceding year (area under curve >0.85), with sensitivity/specificity highest for the FROP‐Com assessment (cut‐off ≥12), sensitivity=0.84 and specificity=0.73. Conclusions: Falls are common in older Indigenous Australians. The FROP‐Com falls risk assessment tool appears useful in this population, and this research suggests changes that may improve its utility further.